2013
DOI: 10.7567/jjap.52.05ee03
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of NOx Reduction by Low Temperature Oxidation Using Ozone Produced by Dielectric Barrier Discharge

Abstract: NO x reduction by low temperature oxidation using ozone produced by a dielectric barrier discharge generator is investigated for different process parameters in a 6 m long reactor in serpentine arrangement using synthetic dry flue gas with NO x levels below 500 ppm, flows up to 50 slm and temperatures up to 80 °C. The role of different mixing schemes and the impact of a steep temperature gradient are also taken into consideration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Some ozone may be consumed by reaction 12 but its contribution is negligible because the rate constant for this reaction (8.43 Â 10 7 exp(À4.908/RT), where R is 1.987 kcal/mol K, and T is K) is very slow compared to that of reaction 11 (rate constant: 2.59 Â 10 9 exp(À3.176/RT)) [27]. Therefore, one mole of ozone formed consumes almost one mole of NO through reaction 11 in the case of indirect plasma treatment which is in agreement with earlier literature [18,[27][28][29][30].…”
Section: Discussionsupporting
confidence: 90%
“…Some ozone may be consumed by reaction 12 but its contribution is negligible because the rate constant for this reaction (8.43 Â 10 7 exp(À4.908/RT), where R is 1.987 kcal/mol K, and T is K) is very slow compared to that of reaction 11 (rate constant: 2.59 Â 10 9 exp(À3.176/RT)) [27]. Therefore, one mole of ozone formed consumes almost one mole of NO through reaction 11 in the case of indirect plasma treatment which is in agreement with earlier literature [18,[27][28][29][30].…”
Section: Discussionsupporting
confidence: 90%
“…Although N 2 O 5 cannot be measured quantitatively using the existing flue gas analyzer, its infrared absorption spectra can be obtained. [6][7][8]19 A second ozone analyzer (model 205, 2B Technologies; 0−200 ppm, ±1 ppb) was used to detect the leftover ozone concentration after the reaction chamber.…”
Section: Methodsmentioning
confidence: 99%
“…The simultaneous removal of SO 2 and NO x by ozone oxidation has been investigated previously. , During the process, NO was first converted to NO 2 when the molar ratio of O 3 /NO was less than 1.0 . However, the NO 2 absorption efficiency was usually lower than expected in limestone slurry at typical WFGD conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when the power supply voltage reaches 150 V under the N 2 , O 2 , NO, and NO 2 system, the NO removal efficiency is 100%. Stamate [26] found that when the input power of the plasma reactor is less than 175 W, the ozone in the reactor is mainly consumed by the oxidation of NO to NO 2 , and NO decreases sharply as the power increases. When the input power is greater than 175 W, NO is completely oxidized, and NO 2 starts to be slowly oxidized to N 2 O 5 , and the NO 2 content decreases.…”
Section: Spectral Diagnosismentioning
confidence: 99%